GAMIFICATION FRAMEWORK FOR SOFTWARE DEVELOPMENT PROJECT PROCESSES (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
Gamification methodology has a positive impact on software development (SD) processes, contributes to better product quality production and team involvement. To show how gamification can be used to motivate the SD project team to carry out daily routine activities and document it in PM tool the gamification framework is proposed in this paper. With this gamification framework is also tried to solve project manager challenge to get actual information in PM tool entered by the project team for correct reporting of project status and process overview. A prototype of a gaming tool has been developed, which is based on Jira's app functionality and is implemented as a plugin.